EFFECT OF LEKHANA BASTI IN THE MANAGEMENT OF DYSLIPIDEMIA: A CLINICAL STUDY - B.A, Pooja; Bhatted, Santoshkumar; K.Bhojani, Meera (International Journal of Ayurveda and Pharma Research, 2015)
Dyslipidemia one of the life style disorder due to the todays faulty life style. It may be manifested by elevation of the total cholesterol the bad low density lipoprotein (LDL) cholesterol and the triglyceride concentrations and a decrease in the good high density lipoprotein (HDL) cholesterol concentration in the blood. Dyslipidemia is widely regarded as a major risk factor for coronary heart disease (CHD) and atherosclerotic cardiovascular disease (ASCVD). Every 1% increase in cholesterol level there is 1-2% increase in the incidence of Coronary Heart Disease.Lipids can be correlated to that of Medo Dhatu. According to the scattered references Dyslipidemia can be correlated to Medo Dosha and subsequently as Medoroga. The treatment principles mainly includes Samshodhana Chikitsa (Bio cleansing), where as in modern statins are first choice of drug.Looking into the adverse reactions and the limitations in the modern medication clinical trial was carried out in 30 patients having Dyslipidaemia. Lekhana Basti was administered and the effect of treatment on the complete lipid profile i.e., Serum cholesterol, Triglycerides, HDL, S.LDL, VLDL was assessed after the treatment and follow up. As Basti Karma is best treatment for correction of Vata Dosha, which are the basic factors involved in the pathogenesis of Medoroga. Statistical analysis using ANOVA and paired t test showed highly significant result in the lipid profile after the treatment and follow up.